(untitled) (Comprehensive Journal of Science, 2025)
The purpose of this study was to evaluate water quality in three different locations in north eastern Libya and was done by the assessment of some physiochemical and microbiological parameters. The chemical evaluation focused on parameters that indicates water quality including pH, alkalinity, heavy metal contamination, and conductivity. Additionally, biological status of these samples has been evaluated. The warning signs provided by authorities in the ancient city of Shahat indicated that Ain Apollo water is not potable. However, no more details were given specifying whether it is chemical, microbial, or other types of pollution. Because of the historical importance of the ancient Libyan cities, we chose to collect samples from three cities including Tolmeitha (Ptolemais), Benghazi (Hesperides/Berenice originally Euesperides), and Shahat (Cyrene). Results show that the lead metal exceeded the local and international limits. However, other metals including cadmium, nickel, copper, and iron were in the acceptable range. No acid rain was found in Tolmeitha, and the pH levels for the surface water samples were acceptable. As for bacteriological analysis, there was no indication for the presence of Total Coliform (T.C.F), Escherichia Coli (E.Coli), and Streptococcus Faecalis bacteria.